Effects of sodium bicarbonate, caffeine, and their combination on repeated 200m freestyle performance - Pruscino, C. L.; Ross, M. L. R.; Gregory, J. R.; Savage, B.; Flanagan, T. R. (International Journal of Sport Nutrition and Exercise Metabolism, 2008)
The purpose of this study was to investigate the effects of sodium bicarbonate (NaHCO3), caffeine, and their combination on repeated 200-m freestyle performance. Six elite male freestyle swimmers ingested NaHCO3 (0.3 g/kg; B), caffeine (6.2 ± 0.3 mg/kg; C), a combination of both (B+C), and placebo (P) on 4 separate occasions before completing 2 maximal 200-m freestyle time trials (TT1 and TT2) separated by 30 min. No significant differences (p = .06) were observed for performance in TT1 (B 2:03.01 ± 0:03.68 min, C 2:02.42 ± 0:03.17 min, B+C 2:01.69 ± 0:03.19 min, P 2:03.77 ± 0:03.21 min) or TT2 (B 2:02.62 ± 0:04.16 min, C 2:03.90 ± 0:03.58 min, B+C 2:01.70 ± 0:02.84 min, P 2:04.22 ± 0:03.75 min). The drop-off in performance time from TT1 to TT2, however, was significantly greater when C was ingested than with B (-1.5%, p = .002) or B+C (-1.2%, p = .024). This is likely because of the lower blood pH and slower recovery of blood HCO3 post-TT1 after C ingestion. These findings suggest that the ergogenic benefit of taking C alone for repeated 200-m swimming performance appears limited. When combined with NaHCO3, however, its negative impact on repeated maximal exercise performance is reversed.